Finite-Time Control Design for a Coaxial Tilt-Rotor UAV - Lv, Zongyang; Zhao, Qing; Sun, Xi-Ming; Wu, Yuhu (IEEE transactions on industrial electronics (1982), 2024)
Coaxial tilt-rotor (CTR) unmanned aerial vehicle (UAV) is a system with the specific configuration of two CTR modules and a rear-rotor module. The CTRUAV is a typical strongly coupled, nonlinear, and underactuated system whose control performance is always adversely affected by various disturbances. To realize robust, stable, and efficient flight control for the CTRUAV is a challenging task. A multivariable cascaded finite-time (FT) controller and an improved nonlinear control allocation law with variable parameters are proposed based on the particular configuration of the CTRUAV. Finally, the superiority and the relationship between the control performance of the proposed control scheme and the control parameters are demonstrated through simulations and real flight experiments. The results show that the proposed control system significantly improves the robustness, transient performance, stability, and efficiency of the CTRUAV. In the flight tests, the root mean square error of the velocity is reduced by 28% in the presence of external disturbance, and the settling time of the attitude is shortened up to 55.8% in tracking the step signal.